A BREIF SURVEY OF ETHNIC VIOLENCE OR CONFLICTS IN THE NORTH EAST INDIA - James, Woba (QUAERENS: Journal of Theology and Christianity Studies, 2023)
This paper is mainly an attempt to present briefly the historical facts and the nature of ethnic violence in the region and not an attempt to interpret them or provide solutions for them as such but to trigger a meaningful time of collective interaction from the pro-peace activists and participants present here. This paper uses a historical survey method. The result of this paper is that ethnic violence in the Northeast region can be attributed to various factors - land alienation, large and continuous influx of immigrants, struggle for space, homeland and struggle for natural resources in the same geographical space, problems of majority and minority populations, insurgency conflicts, and others. Thus, it becomes clear that peace can be restored in the region only through the restoration of people's land and cultural identity, socio-political autonomy, poverty alleviation, education, and development, especially in rural areas.